KEKUATAN DAN TANTANGAN PENGAJARAN KRISTEN TENTANG PERNIKAHAN DALAM PERSPEKTIF JEMAAT GMAHK PUTRA AGUNG SURABAYA - Daniel Siswanto; Rudolf Sagala; Stimson Hutagalung (SEKOLAH TINGGI TEOLOGI STAR'S LUB LUWUK BANGGAI, 2021)
This study aims to explore the congregation's understanding of the concept of marriage and to see the potential for divorce. The method used is a survey using a questionnaire. The research subjects were the Seventh-day Adventist Church, Putra Agung Congregation Jl. Karang Asem IV No. 6 Surabaya. The selected respondents were adult congregations, totalling 177 people. The sampling technique used was a quota sampling of 50% of the total adult congregations. The data were analyzed by making claims on the tendency of respondents' answers. The results show that the congregation's understanding of marriage is by Christian teachings, which highly respect marriage and reject divorce. However, the potential for divorce is still there, as seen from the small number of respondents who do not dare to ensure that they will not divorce if there are problems in the household.